Déficit fiscal e inflación en el Perú (1980-2010). - Solano Coello, Rolando Gilmer (2011)
This document seeks to show the happened in to act of the public sector during the last thirty years, exploring for them the factors that determined the fiscal deficit and the inflation during this period, and especially trying to demonstrate the response of the inflation to the form in which it has been an agreement the financing of the fiscal deficit in the above period mentioned. The principal aim of the work is to analyze the influence of the fiscal deficit in the evolution of the inflation in the Peruvian economy from 1980 until 2010. In this work also there is discussed the hypothesis that it has to see with some relevant facts of the public expenditure that have affected in a positive way in the evolution of the inflation in the period of study. The proposed hypothesis is proved using a quantitative approach, which results are the empirical checking of which the evolution of the inflation has been influenced by the development of the public sector, basically expressed by the fiscal deficit, having periods of major influence, since it is the decade of 1980, where the fiscal deficit was financed by monetary emission, and period of minor influences where the deficit was financed by other sources of financing. Besides it we use a model econometric to describe the behavior of the inflation explained by the behavior of the fiscal deficit. Finally, it comes near to the conclusion of which the inflation in Peru has seen influenced by the deficit of the public sector, principally owed to the form in which this one was financed, existing two period differentiated, the first one the decade of 1980, where the fiscal deficit was financed by monetary emission and, the decade of 1990 in forward where the fiscal deficit was financed by other sources of financing different from the emission.